Early stress during NICU stay and parent-reported health-related quality of life after extremely preterm birth: an exploratory study with possible targets for early intervention - van Dokkum, Nienke H.; Bos, Arend F.; Kraft, Karianne E.; Bouma, Helene A.; Reijneveld, Sijmen A.; Krabbe, Paul F. M.; de Kroon, Marlou L. A. (Frontiers in Pediatrics, 2024)
Introduction The association between neonatal intensive care unit (NICU) related stress in preterm infants and their health-related quality of life (HRQoL) in the first year following preterm birth remains unexplored. Understanding this association is crucial for enhancing preventive and supportive measures for infants and parents within and beyond the NICU. Methods From a single center observational cohort study, we included infants with gestational ages below 30 weeks and/or birth weights under 1,000 grams. HRQoL was quantified using the Infant Quality of Life Instrument (IQI) at 3-, 6-, 9- and 12-months corrected age, covering seven domains. NICU stress was quantified using the Neonatal Infant Stressor Scale (NISS) for the first week of life. We performed Spearman's correlation analyses to test this association. Results Of the 45 included infants, the IQI was completed for 27 (60%) at 3, 15 (33%) at 6, 14 (31%) at 9 and 15 (33%) at 12 months. The HRQoL sum scores were related to neonatal stress at 9 and 12 months (ρ = 0.643 and 0.591, p = 0.013 and p = 0.019, respectively) but not at 3 and 6 months (ρ = −0.001 and −0.077 respectively, p > 0.05). Higher NICU stress tended to be associated with more respiratory and mood problems throughout the first year. Discussion From a parental perspective on infant HRQoL, extremely preterm infants with higher stress exposure show more problems in the second half-year of life, mainly breathing and possibly mood-related problems. This knowledge may help improve our neonatal care, both during NICU stay and in follow-up clinics, by implementing targeted interventions.